2021
DOI: 10.1007/s11547-021-01375-3
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal ramp lesions: diagnostic performance of MRI with arthroscopy as reference standard

Abstract: Background The posteromedial meniscal region is gaining interest among orthopedic surgeons, as lesions of this area has been reported to be significantly associated with anterior cruciate ligament tears. The current imaging literature is unclear. Purpose To evaluate the diagnostic performance of MR in the detection of meniscal ramp lesions having arthroscopy as reference standard. Materials and methods We retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) is regarded as the best imaging modality to diagnose meniscal ramp lesions [ 10 , 14 , 43 , 44 ], even though its accuracy has been questioned due to the varying sensitivity reported in previous studies [ 2 , 11 , 19 , 41 ]. In their recent systematic review and meta-analysis, Koo et al [ 21 ] reported that MRI has high specificity (94%) but moderate sensitivity (71%) for diagnosing ramp lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is regarded as the best imaging modality to diagnose meniscal ramp lesions [ 10 , 14 , 43 , 44 ], even though its accuracy has been questioned due to the varying sensitivity reported in previous studies [ 2 , 11 , 19 , 41 ]. In their recent systematic review and meta-analysis, Koo et al [ 21 ] reported that MRI has high specificity (94%) but moderate sensitivity (71%) for diagnosing ramp lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the data were obtained from two different institutions without a unified protocol for diagnosing LMPRT and MM ramp lesions, and assessing whether an ACL was completely or incompletely torn, as they would be influenced by the surgeons' assessment. However, the diagnosis and classification of LMPRT and MM ramp lesions in the literature were still in continuous development and evolution during the study period [16, 43, 46]. Third, MRI scans were not completely controlled for quality (1.5 T and 3.0 T) and the determination of the direction and cranial‐caudal range, which could limit some measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI criteria put forth by Zappia et al 32 were used to define the presence of a ramp lesion in this study. These criteria have exhibited excellent sensitivity, specificity, and interreader reliability for the detection of ramp lesions on MRI relative to arthroscopically confirmed ramps through a posteromedial portal.…”
Section: Methodsmentioning
confidence: 99%
“…These criteria have exhibited excellent sensitivity, specificity, and interreader reliability for the detection of ramp lesions on MRI relative to arthroscopically confirmed ramps through a posteromedial portal. 32 On MRI, medial meniscal ramp lesions were defined as a vertical (longitudinal) tear of the peripheral capsular attachment of the posterior horn of the medial meniscus at the meniscocapsular junction. Zappia et al’s criteria for diagnosing the presence of a ramp lesion on MRI included if the concave band (ramp capsule) with low signal intensity posterior to the posterior horn of the medial meniscus was interrupted by a line of hyperintensity crossing this capsular reflection.…”
Section: Methodsmentioning
confidence: 99%